Penanganan Gawat Darurat Tension Pneumothorax Dengan Needle Thoracocentesis ICS ke-5 & Pemasangan Mini-WSD: A Case Report - Ricat Hinaywan Malik (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Tension pneumothorax is an emergency with high mortality rate that can be handled with simple action. Besides due to many thoracic trauma, tension pneumothorax is rarely caused by infectious diseases such as pulmonary tuberculosis. During this time, the treatment is with needle thoracocentesis in the second intercostal space in mid-clavicle line and installation of chest tube-WSD in the fifth intercostal space. Objective: To discuss emergency treatment with limited facilities and resources in tension pneumothorax patients using needle thoracocentesis in the fifth intercostal space in mid-clavicle line and mini-WSD installation. Methods: Case report, case choosed from a rare case that emergency which patient treated and can survive until discharge from hospital with limited facilities and resources. Results: A 38-year-old man was admitted to a hospital ward with shortness of breath that was getting heavier the last week, coughing up sparse phlegm, and a fever. Physical examination: composmentis, normal blood pressure, HR 132x/min, RR 34 x/min, temperature 37,5oC, SpO2 80%. There is an increase in JVP, asymmetric chest (left higher than right), right chest motion left behind, no chest pain, hypersonor right chest, right chest auscultation sounds like air passing through water pipe, left chest sounded roughly crackles. Support: leukocytosis, HIV positive on VCT, chest X-ray showing severe right pneumothorax and left pulmonary tuberculosis. Patient was diagnosed with tension pneumothorax secondary to pulmonary tuberculosis, other than AIDS. Emergency needle thoracocentesis is performed in the right fifth intercostal space, mid-axilla line just above the 6th rib, and connected with mini-WSD. The result is clinical improvement. Patient was survive until definitive action and further treatment can be taken by the experts. Conclusion: The needle thoracocentesis of the fifth intercostal space in mid-axilla line and mini-WSD is easier to perform and improve the clinical state of tension pneumothorax patient. Keywords: thoracocentesis; decompression; intercostal space; mini-water sealed drainage; secondary tension pneumothorax ABSTRAK Latar Belakang: Tension pneumothorax merupakan keadaan gawat darurat dengan angka kematian tinggi yang bisa ditangani dengan tindakan sederhana. Selain banyak disebabkan karena trauma toraks, tension pneumothorax jarang disebabkan penyakit infeksi seperti tuberkulosis paru. Selama ini penanganannya dengan needle thoracocentesis di sela iga kedua linea mid-klavikula dan pemasangan chest tube-WSD di sela iga kelima. Tujuan: Mendiskusikan penanganan emergensi dengan keterbatasan fasilitas dan sumber daya pada pasien tension pneumothorax menggunakan needle thoracocentesis di sela iga kelima linea mid-klavikula dan pemasangan mini-WSD. Metode: Laporan Kasus, kasus dipilih dari kasus emergensi yang jarang terjadi berupa kasus emergensi dimana pasien diberi penanganan dan dapat bertahan hidup hingga pulang dari rumah sakit dengan keterbatasan fasilitas dan sumber daya. Hasil: Seorang laki-laki, 38 tahun, dirawat di bangsal rumah sakit dengan sesak nafas yang semakin memberat 1 minggu terakhir, batuk berdahak jarang, dan demam. Pemeriksaan fisik: komposmentis, TD normal, HR 132x/min, RR 36 x/min, suhu 37,5oC, SpO2 80%. Terdapat peningkatan JVP, dada asimetris (kiri lebih tinggi dibanding kanan), gerak dada kanan tertinggal, tak ada nyeri tekan dada, dada kanan hipersonor, auskultasi dada kanan terdengar seperti udara yang melewati pipa air, dada kiri terdengar ronki kasar. Penunjang: leukositosis, VCT positif HIV, foto toraks menunjukkan pneumotoraks kanan berat dan TB aktif paru kiri. Pasien didiagnosis tension pneumothorax sekunder karena TB paru, selain AIDS. Dilakukan tindakan emergensi needle thoracocentesis di ICS 5 linea mid-aksila kanan tepat di atas kosta ke-6, dan disambung dengan mini-WSD. Hasilnya terdapat perbaikan klinis. Pasien bertahan hidup hingga dapat dilakukan tindakan definitif dan penanganan lebih lanjut oleh ahlinya. Kesimpulan: Needle thoracocentesis sela iga kelima linea mid-aksila dan mini-WSD lebih mudah dilakukan dan memperbaiki keadaan klinis pasien tension pneumothorax. Kata kunci: torakosintesis; dekompresi; sela iga; mini-WSD; tension pneumothorax sekunder